ORPHANS OF THE JESUITS. THE FAREWELL OF THE COMPANY OF JESUS TO THE KINGDOM AND CITY OF SANTIAGO DE CHILE IN TIMES OF EXPULSION (1767) - Gaune Corradi, Rafael; Rolle, Claudio (Revista de Historia Social y de las Mentalidades, 2020)
Through a document written by an anonymous author - possibly a Jesuit - we analyse the arrival of the decree of estrangement of the Society of Jesus in 1767 by King Charles III. The text, composed of an initial lamentation and an epitaph, relates the pain and lament of the Jesuits in the face of the sensation of injustice and the immeasurability of the future exile. It is marked by the apologetics of their history, the metaphorization of pain and the fear of the future. The anonymous document functions as a farewell to their specific place in the world, but, at the same time, it is a record-monument of their historical journey in Chile that also appeals to their secular tradition in the Catholic world.